KEMAMPUAN EKSTRAK BIJI KELOR SEBAGAI INHIBITOR KOROSI BESI DALAM LARUTAN HCl - Sunarti Sunarti; Victor Kayadoe; Prima D Rahawarin (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2020)
ABSTRACT There was already an experiment to test the capability of moringa seed extract in inhibiting corrosion of iron using the method of weight reduction. Inhibit power is obtained based on the inhibition efficiency of moringa seed extract concentration variation of 1%, 2%, 3%, and 4% as well as temperature variations, namely 35, 40, 45, and 50 based on the results of research obtained the data and the rate of corrosion inhibition efficiency the concentration variation in a row l: 82.92%; 86.87%; 91.02%; 93.74% and 0.4342; 0.3032; 0.2235; 0.1710.In the temperature variation data obtained and the rate of corrosion inhibition efficiency in a row